1986
DOI: 10.1111/j.1445-5994.1986.tb00034.x
|View full text |Cite
|
Sign up to set email alerts
|

Inobvious Stroke: A Cause of Delirium and Dementia

Abstract: Six hundred and sixty-one patients with stroke, confirmed by CT scan or at autopsy, were reviewed in order to evaluate the frequency of presentation with altered mental state. Nineteen patients (3%) had presented with delirium, an organic delusional state, the acute onset of dementia, or mania, mimicking psychiatric illness. All had focal cerebrovascular lesions which were usually, but not invariably, right sided. None had a previous history of cognitive impairment, psychiatric disease, drug abuse, or alcohol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
1
4

Year Published

1989
1989
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(39 citation statements)
references
References 6 publications
1
33
1
4
Order By: Relevance
“…The designs employed in the studies included in this review were prospective studies (n=11), retrospective studies (n=3) case controls (n=3), one cross sectional study, one pilot study of treatment intervention and one study which was described as "observational" (see table 2). A total of 12 studies reported applying established diagnostic criteria when assessing patients for delirium: Six (30%) studies applied DSM IV[2, [23][24][25][26][27], three (15%) studies applied DSM III-R [28][29][30], two studies applied DSM IV-R [31,32], and one (5%) study applied DSM III [33]. Three studies referred to "clinical assessment" but did not detail any diagnostic guidelines [34][35][36], and one study referred to the diagnosis of "disorientation" using a simple 3 point scale [37].…”
Section: Description Of Studies Included In This Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“…The designs employed in the studies included in this review were prospective studies (n=11), retrospective studies (n=3) case controls (n=3), one cross sectional study, one pilot study of treatment intervention and one study which was described as "observational" (see table 2). A total of 12 studies reported applying established diagnostic criteria when assessing patients for delirium: Six (30%) studies applied DSM IV[2, [23][24][25][26][27], three (15%) studies applied DSM III-R [28][29][30], two studies applied DSM IV-R [31,32], and one (5%) study applied DSM III [33]. Three studies referred to "clinical assessment" but did not detail any diagnostic guidelines [34][35][36], and one study referred to the diagnosis of "disorientation" using a simple 3 point scale [37].…”
Section: Description Of Studies Included In This Reviewmentioning
confidence: 99%
“…There was no attempt in any of the studies to assess the suitability of using a generic delirium screening tool in acute stroke. A number of studies considered the challenge of using the above tools in acute stroke, as ten studies reported excluding patients with reduced consciousness [23,27,29,30,32,33,[36][37][38][39] and four studies excluded patients with aphasia [24,26,29,36]. Caeiro et al reported scoring zero in certain items of the DRS if patients had "language difficulties" [23,31,32], however, this term is somewhat vague.…”
Section: Diagnostic and Screening Tools Usedmentioning
confidence: 99%
See 3 more Smart Citations